Penerapan Teknologi Informasi Desain Kemasan Produk Kripik dan Donat Desa Gedung Pekoun Kecamatan Lengkiti Kabupaten OKU - Destiarini Destiarini; Abdul Rahman; Azwar Azwar; Lucyana Lucyana; Eka Rizki Mewinda (Universitas Dehasen Bengkulu, 2023)
Industry 4.0 offers tremendous technological advances and has a significant impact on community institution services at the village level. Currently, many improvements have been made in the village related to community services, one of which is technology and information services. Government information must be made public quickly, as information has an expiration date. The information conveyed is certainly very useful for the village community, so it is necessary to do socialization quickly and precisely. The purpose of this activity is to increase the creativity of village officials and community members in making media. Packaging design training to convey information and other village activities to promote such activities. Package design training is considered very necessary to increase the creativity of village officials and the communities that represent them. The proposed solution is to provide packaging graphic design training assistance to residents of Gedung Pekoun Village, Lengkit District, Ogan Kemering Ulu Regency.